Mylar Secondary Emission-energy Distribution and Yields - Fonzar Pintao, Carlos Alberto (Institute of Electrical and Electronics Engineers (IEEE), 2014)
We have characterized Mylar by determining the emission yield and energy spectrum of emitted secondary electrons. In this study we used a conventional electron accelerator apparatus to which we have made some important adjustments, especially to determine the normalized energy distribution. These adjustments allowed us to obtain the data necessary to calculate reduced yield curves, (delta/delta(M) vs. E/E-M) in which the secondary emission yields and the Energy of the fixed energy beam were both divided by their maximum values. Results for the total emission yield (sigma), backscattered electrons (eta) and true secondary emission electrons (delta) were obtained as a function of the energy of the incident electron beam (E). The results from an experiment where the incident beam was vertically striking a Mylar sample (thickness 36 mu m) are presented. The location of the first and second crossover points, where delta=1, as well as the energy spectrum of secondary electron emission using a planar symmetry arrangement for energies of 1.2 and 1.4 keV were obtained and presented.
Keywords: Secondary electron emission; emission yields; electron beam; secondary energy spectrum; mylar; reduced yield curves; dielectrics; crossover points; electron accelerator; polymers